The change of administrative capacity in Korea: contemporary trends and lessons. (June 2021) - Ko, Kilkon; Park, Hyun Hee; Shim, Dong Chul; Kim, Kyungdong
This article empirically explores the understanding and changes in the concept of administrative capacity in the Korean context. Despite a universal consensus on its importance, administrative capacity is defined differently by regimes and stakeholders (i.e. in this study: the public, members of the National Assembly, and academia). To improve our understanding of administrative capacity, we collected three types of texts (337 academic papers, 1470 National Assembly minutes, and 3316 newspaper articles from 2000 to 2019) and analyzed the data using topic modeling and text-network analysis methods. The results suggest that although academic articles emphasized leadership, manpower, education, and other policymaking capacities, the National Assembly stressed innovation capacity in solving different policy problems. Finally, the media, assumed to reflect public opinion, emphasized capacities related to national security. Points for practitioners: This study suggests that different types of administrative capacities could be needed according to the developmental stage of states. While managerial and administrative capacity should be developed in countries pursuing state-led economic development, governance capacity could be more requested in countries facing demands for democratization and meeting citizens' various needs and participation.